A retrospective observational study on case reports of adverse drug reactions (ADRs) to tirzepatide - Huang, Mengmeng; Liu, Guangwei; Zhang, Chuanzhou; Wang, Ying; Liu, Shengfen; Zhao, Jun (Frontiers in Pharmacology, 2025)
BackgroundWith the increasing clinical use of tirzepatide, its safety profile has garnered significant attention. This article systematically reviews case reports of tirzepatide-associated adverse drug reactions (ADRs) to summarize their characteristics.MethodWe searched PubMed, Web of Science, ScienceDirect, Wiley Online, and Embase databases for case reports on tirzepatide adverse events using the keywords: “tirzepatide”, “adverse reaction”, “adverse event”, “side effect”, “safety”, “case report”, “induced”, “associated”, and “related”. Statistical analysis was performed on the identified cases.ResultsA total of 43 cases of tirzepatide ADR were identified from 37 articles. Among these patients (24 female, 19 male; mean age 50.23 ± 17.24 years), 19 involved concomitant medications affecting multiple systems. ADR was reported in each dosage of tirzepatide, with the most occurring at 2.5–5 mg (16 cases), and primarily occurred within 1–6 months of initiation. Regarding rechallenge, 15 patients discontinued tirzepatide, three continued use, and one reduced the dose. ADR involved seven gastrointestinal tract and endocrine systems, including liver and gallbladder, circulation, nerve, skin, and urinary. Notable manifestations included ketoacidosis, liver injury, hypotension, intestinal obstruction, and allergic reactions. Among them, ketoacidosis and common peroneal neuropathy causing foot sagging, acute appendicitis, lower limb venous thrombosis, gastric outlet obstruction, gastric emptying delay, and acute liver injury were not mentioned in the drug instructions. ADR correlation assessment was performed for 8 patients:4 cases of cardiovascular events and ketoacidosis were all evaluated as “probable” using the Naranjo scale, 3 cases of liver injury were assessed by RUCAM (2 case as “possible”, 1 cases as “probable”), 1 case did not specify the evaluation method, with the result being “highly probable”. All 43 patients underwent ADR correlation re-evaluation:32 cases (74.42%) were assessed as “probable”,11 cases (25.58%) were assessed as “possible”.ConclusionTirzepatide-associated ADRs most commonly occur within the first 6 months of treatment, primarily affecting the digestive, endocrine, liver, and gallbladder systems. Enhanced monitoring of liver and kidney function is warranted, especially in patients concurrently taking other potentially hepatotoxic or nephrotoxic medications. Additionally, intensified therapeutic drug monitoring is recommended for patients with cardiovascular disease, those requiring weight-based dosing adjustments, and those experiencing rapid weight loss.